2012
DOI: 10.1111/j.1529-8019.2012.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives for the treatment of local advanced disease: electrochemotherapy, limb perfusion, limb infusion, intralesional IL2. What is the role?

Abstract: Nowadays, melanoma is one of the most common fatal malignancy of young adults. Incidence is increasing, but mortality rates from melanoma have remained stable. In-transit metastases from extremity or trunk melanoma are subcutaneous or cutaneous deposits of melanoma distant from the primary site, but not reaching the draining nodal basin. According to American Joint Committee on Cancer classification of stages based on Tumor, Node, Metastases classification stages IIIb and IIIc are considered local advanced dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Early clinical studies were conducted in patients with in-transit metastatic melanoma [31][32][33][34][35]. Following the publication of the ESOPE study results, several additional studies have been conducted since and lead to identification of ECT role in patients with stage III and IV melanoma [66,[74][75][76][77][78][79][80][81]. The involvement of patients' immune cells after ECT has suggested to investigated the effect of combining ECT treatment with systemic immunomodulating agents in melanoma patients [27,82].…”
Section: Clinical Experiencesmentioning
confidence: 99%
“…Early clinical studies were conducted in patients with in-transit metastatic melanoma [31][32][33][34][35]. Following the publication of the ESOPE study results, several additional studies have been conducted since and lead to identification of ECT role in patients with stage III and IV melanoma [66,[74][75][76][77][78][79][80][81]. The involvement of patients' immune cells after ECT has suggested to investigated the effect of combining ECT treatment with systemic immunomodulating agents in melanoma patients [27,82].…”
Section: Clinical Experiencesmentioning
confidence: 99%
“…The electric pulse creates cell membrane poration resulting in a better penetration of the chemotherapeutic agent. [52,53] A study has reported a 72% objective response rate of the total of 54 lesions treated with electrochemotherapy. [53] However, superiority of one over the other has not been proven and the choice of the method depends on individual factors.…”
Section: Surgery Of Locoregional Recurrence Of Melanomamentioning
confidence: 99%
“…Repeat ILI has demonstrated similar ORR as initial ILI and is offered to patients with unresectable disease recurrence who previously demonstrated a response with an initial ILI or ILP (21). Other therapies such as electrochemotherapy (ECT) and intralesional immunotherapy have also shown promise, although long-term efficacy remains to be determined (22, 23). …”
Section: Discussionmentioning
confidence: 99%